Galectins in Glioma: Current Roles in Cancer Progression and Future Directions for Improving Treatment - Samy Ajarrag (MDPI AG, 2021)
Traditional wisdom suggests that galectins play pivotal roles at different steps in cancer progression. Galectins are particularly well known for their ability to increase the invasiveness of cancer cells and their resistance to drug-induced cell death. They also contribute to the development of local and systemic immunosuppression, allowing cancer cells to escape the host’s immunological defense. This is particularly true in glioma, the most common primary intracranial tumor. Abnormally high production of extracellular galectins in glioma contributes to the establishment of a strong immunosuppressive environment that favors immune escape and tumor progression. Considering the recent development and success of immunotherapy in halting cancer progression, it is logical to foresee that galectin-specific drugs may help to improve the success rate of immunotherapy for glioma. This provides a new perspective to target galectins, whose intracellular roles in cancer progression have already been investigated thoroughly. In this review, we discuss the mechanisms of action of galectins at different steps of glioma progression and the potential of galectin-specific drugs for the treatment of glioma.